Problematika Pondok Tahfiz Al-Qur’an - Abdul Jalil (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: Huffazh face various challenges related to conditions prevailing in the society in recent times. Hafidh al-Qur’an role in society is limited enough to be on social-religious space, which is just at the religious rituals, such as mortality events, weddings, and other ceremonies. Plus, the interest of the public to explore the religious sciences also have declined. Also challenges related to scientific odyssey and the skills acquired during the Qur’an hafizh enrolled in PTQ. PTQ education in Indonesia is still limited to science qira’ah and memorization alone, not to the deepening of the Qur’an Ulumul comprehensively. Plus, the appreciation given to the hafidhul Qur’an, from educational institutions outside the PTQ to develop scientific knowledge, is also inadequate. In this paper the author will present a glimpse of the Koran on the development of science and some problems in the PTQ and suggestions and responses to the problems. Keywords : al-Qur’an, problems, Hafidh.